Seepage Behaviour of Fractured Rock Mass Infilling Using Different Transfixion Rates under Cyclic Loading. (10th May 2021) - Wang, Shuren; Zhang, Jiyun; Li, Zhichao; Yu, Yongqiang
Abstract : It is very important to determine the seepage behaviour of fractured rock mass infilling to evaluate the stability of the surrounding rock. The joint transfixion rate is the ratio of the unpenetrated length to the penetration length of a joint in a sample. Samples of the fractured rock mass infilling using different transfixion rates were prepared, and a TCQT-III low-permeability coal-rock triaxial seepage device was used to conduct three cycles of confining pressure-seepage coupling tests. Results show that the permeability is a power function in the confining pressure of the sample, and the permeability changes most significantly with the confining pressures. The permeability of the sample increases exponentially with the joint transfixion rate. The permeability loss is positively correlated with the plastic deformation of the sample; the permeability changes most significantly during the first cycle loading. There is over 60% recovery of the permeability of the sample under cyclic loading for loads that do not exceed the strength of the infilling. The stress sensitivity coefficient decreases as the confining pressure increases and is higher during the unloading stage than that during the loading stage for samples with an incomplete transfixion rate. The conclusions obtained in this study can serve as a reference for grouting applications.